Constraints on selfish behavior in plants - Semchenko, Marina (Science (American Association for the Advancement of Science), 2020)
Plants overproduce roots to secure resources nearby but avoid costly trips to neighbors' patches We are used to human behavior, and the actions of other animals, being described as selfish, aggressive, or cooperative. Such words come up less often when contemplating plants. Yet plants too have evolved a fascinating array of behavioral strategies in their struggle for resources, although these are hard to demonstrate and quantify. Whether and when it pays for plants to selfishly overproduce roots and preempt resource capture by competitors, or cooperate by restraining root growth, has been the subject of extended debate ( 1 , 2 ). On page 1197 of this issue, Cabal et al. ( 3 ) tackle this question with a new theoretical model and an empirical test that highlight spatial costs of nutrient foraging as key to resolving apparent discrepancies between previous studies.